Small-Signal Stability Analysis of the Power System Based on Active Support of Renewable Energy VSCs - Chu, Tianfeng; Xu, Miao; Xie, Yu; Wang, Shunjiang; Li, Dianyang; Liu, Gang (Frontiers in Energy Research, 2022)
With the large-scale renewable energy access to the power system, the voltage source converters (VSCs) in the system are gradually increasing. The system inertia is weakened, which leads to the decrease of frequency support ability and affects the stability of the power system. After adopting active support control, VSC-based renewable energy units have inertia support ability similar to traditional synchronous generators (SGs), which can improve the frequency stability of the system. This paper is intended to the control strategy based on active support of renewable energy. Small-signal stability of a two-zone system with different control strategies for VSCs under different conditions is analyzed. At the same time, considering the dynamic adjustment effect of different parameters for active support control. Improving frequency stability of a two-zone system with inertial flexible control. In this paper, the basic principle of active support control is expounded in detail. Compared with PQ-control and droop-control, it is verified that active support control has better frequency support ability. The small-signal model of VSCs for active support and two-machine system is established, respectively. Combined with the simulation system, the influence of virtual inertia and damping coefficient on system stability is verified.